Analisis Efektivitas Pajak Penerangan Jalan Sebagai Sumber Pendapatan Asli Daerah (PAD) Kota Surabaya Tahun 2019-2021 - Sinta Paulina Situmorang; Gideon Setyo Budiwitjaksono (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
Street lighting tax is one of the local taxes that give a great degree contributes to increasing the original local revenue (PAD) of Surabaya City. This study aims to determine the level of effectiveness of the street lighting tax of Surabaya City from 2019 to 2021. This research was conducted at the Regional Revenue Agency (Bapenda) of Surabaya City. The research method used was a qualitative descriptive method, by analyzing data related to the target and realization of Surabaya’s street lighting tax from 2019 to 2021. The data collection used were documentation and interview. The results of the study show that the effectiveness of Surabaya’s street lighting tax in the period 2019 to 2021 has fluctuated. The average percentage of effectiveness from 2019 to 2021 is 96.89% with effective criteria. The effectiveness percentage for the street lighting tax in 2019 is 100.01% with very effective criteria. The percentage of effectiveness in 2020 is 100.17% with very effective criteria. The percentage of effectiveness in 2021 is 90.86% with enough effective criteria. Keywords: Effectiveness, Street Lighting Tax, Original Local Revenue